1973
DOI: 10.1038/bjc.1973.146
|View full text |Cite
|
Sign up to set email alerts
|

Studies Concerned with Overcoming Resistance to Methotrexate: A Comparison of the Effects of Methotrexate and 2,4-Diamino-5-(3′,4′-Dichlorophenyl)-6-Methylpyrimidine (BW50197) on the Colony Forming Ability of L5178Y Cells

Abstract: Summary.-The effects of methotrexate (MTX) and 2,4-diamino-5-(3',4'-dichlorophenyl)-6-methylpyrimidine (BW50197) on the colony forming ability of L5178Y cells were compared. Two sub-lines of cells were used, one sensitive to methotrexate and the other resistant. In addition, the inhibitory effects of BW50197 against dihydrofolate reductase (DHFR) extracted from the MTX resistant-cells were compared with those of MTX and pyrimethamine. It was found that although BW50197 was a less effective inhibitor of DHFR th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Similar results have been obtained by studying the effect of methodichlorophen (2,4-diamino-j- ( 3 ',q'-dichlorophenyl)d-methylpyrimidine) on the colony forming ability of Ls178Y cells, i.e. the methotrexate resistance did not greatly alter the sensitivity to the diaminopyrimidine (Hill et al, 1973) ; cross resistance would have been expected if the two agents shared the same transport system. Direct transport studies with these two diaminopyrimidines indicated competition for uptake with folinic acid but not with methotrexate (B. T. Hill, personal communication).…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have been obtained by studying the effect of methodichlorophen (2,4-diamino-j- ( 3 ',q'-dichlorophenyl)d-methylpyrimidine) on the colony forming ability of Ls178Y cells, i.e. the methotrexate resistance did not greatly alter the sensitivity to the diaminopyrimidine (Hill et al, 1973) ; cross resistance would have been expected if the two agents shared the same transport system. Direct transport studies with these two diaminopyrimidines indicated competition for uptake with folinic acid but not with methotrexate (B. T. Hill, personal communication).…”
Section: Discussionsupporting
confidence: 74%
“…Hill et al [8] demonstrated the toxicity of DDMP in a MTX-resistant L5178Y cell line. Rosowsky et al [17] showed that a MTX transportresistant cell line was still sensitive to MTX esters as well as lipophilic antifolates such as DDMP.…”
Section: Discussionmentioning
confidence: 99%
“…drug uptake, and DHFR activity indicate a correlation between drug sensitivity and levels of bound drug [1][2][3][4]. However, resistance to MTX is also related to the amount of DHFR and its inhibition, in cells where MTX transport is unchanged [5][6][7] studies suggested that lipid-soluble antifolates may be useful in overcoming resistance to MTX due to inabil ity of cells to take up MTX [8,9]. New antifolate compounds, particularly the lipid-soluble analogs, are being extensively studied for use against MTXresistant cells because of their different pharmacologi cal and physicochemical properties relative to MTX [10][11][12][13].…”
mentioning
confidence: 99%
“…Lipid-soluble antifolates could help overcome MTX resistance caused by cells' inability to absorb the drug (Hill et al 1973;Nichol 1968). Because of their distinct pharmacological and physicochemical properties compared to MTX, new antifolate compounds are being investigated for use against MTX-resistant cells (Burchenal et al 1952;Mishra et al 1973;Ho et al 1972;Nichol et al 1977).…”
Section: Introductionmentioning
confidence: 99%